Exploring the physical, mental, and social dimensions of middle-aged adults for active and healthy aging: A cross-sectional study - Eunice Santos; Lara Guedes Pinho; Adelaide Proença; Helena Arco (PLoS ONE, 2025)
Introduction Population ageing presents a significant global challenge, necessitating sustained efforts to promote active and healthy ageing throughout life to improve quality of life in later years. This study aims to characterise the physical, mental, and social well-being of middle-aged adults (aged 55–64) in Baixo Alentejo, Portugal, and to analyse associations between these dimensions and sociodemographic variables. The findings aim to inform policies and interventions supporting active and healthy ageing, a cornerstone for quality longevity. Methodology This cross-sectional, descriptive study was conducted between 02 May 2023 and 29 February 2024 among individuals aged 55–64 registered at health centres in Baixo Alentejo, Portugal. Data were collected via a structured questionnaire evaluating disability, depressive symptoms, life satisfaction, and satisfaction with social support. Instruments included the WHO Disability Assessment Schedule (WHODAS 2.0-PT12), the Patient Health Questionnaire (PHQ-9), a self-reported life satisfaction score, and the Social Support Satisfaction Scale (SSSS). Statistical analysis employed Student’s t-test and one-way ANOVA. Ethical approval was obtained, and all participants provided informed consent. Results The study included 698 participants. Women, individuals with lower educational attainment, and the unemployed demonstrated significantly higher functional disability scores. Women and unemployed participants also had higher depressive symptom scores. Conversely, men reported greater life satisfaction. Older participants and those with lower socioeconomic status exhibited greater physical limitations, depressive symptoms, and dissatisfaction with social support. Economic stability was positively associated with mental well-being and life satisfaction, underscoring the importance of financial security in enhancing perceptions of social support. Conclusion This study provides a comprehensive characterisation of middle-aged adults in Baixo Alentejo, revealing significant associations between sociodemographic factors and physical, mental, and social well-being. The findings highlight the need for tailored socioeconomic and health interventions to promote active and healthy ageing. Public policies designed to address the unique needs of middle-aged adults in the region are critical to improving health outcomes and fostering quality longevity.